DETEKSI PERUBAHAN GARIS PANTAI DENGAN METODE BILKO DAN AGSO (STUDI KASUS KAWASAN PANTAI SELATAN PROVINSI DAERAH ISTIMEWA YOGYAKARTA TAHUN 1997 SAMPAI TAHUN 2012) - Cahyani, Septian Dewi; Suprayogi, Andri; Awaluddin, Moehammad (Departement Teknik Geodesi Universitas Diponegoro, 2012)
Coastline change detection in Yogyakarta Province conducted in 15 years (1997-2012) utilizing Landsat satellite imagery in 1997, 2002, 2006, and 2012. According to Sudarsono, 2011 coastline is the meeting between the shore (land) and water (ocean). A certain water level was chosen to explain the position of the coastline, the water line (high water line) as the coastline and the line of low water (low water line) as a reference depth. The conclusion from the results of digitization and validation using GPS handeld tracking in the field in 2012 with Landsat image data are applied to the formula BILKO and AGSO obtained the best accuracy values ​​of 95% for BILKO formula. Average coastline change from the best formula is (1) Average coastline change in 1997-2002 caused by the abrasion of 212.20 Ha, and average result of the accretion of 107.89 Ha. (2) Average coastline change in 2002-2006 caused by the abrasion of 287.00 hectares, and average result of the accretion of 236.89 Ha. (3) Average year 2006-2012 coastline changes that occur due to abrasion of 379.50 Ha, and average result of the accretion of 250.07 Ha. Key words : Landsat Satellite Imagery, Coastline Change